Design, anläggningsmetoder och skötseltekniker för hagmarksbestånd - Svensson, Jenny (2008)
There is many valuable nature and culture landscapes in Sweden that has developed during a long period of time, throw natural processes or human use. Unfortunately lot of these are disappearing. My thought with this work is to explore the possibility to establish new areas with similar qualities. The motive for this is that attractive countryside biotopes are well worth to use as model to enrich the urban landscape. Another thought has concerned the people that establish, build and manage landscapes and parks. They often have varied views, both coming from a difference in background and previous experiences. That fact is likely to effect their work. The purpose is to discuss and compare different professions view of the problem presented above, to compare and discuss potential differences and the reasons for them.